Supply Chain Management in Industrial Companies: Performance Assessment Model - Hartanto, Soni (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this research is to study the current measurement of supply chain management framework and to find gaps in previous research to develop a more precise measurement framework in industrial supply chain management strategy. The method used in this study is a systematic literature review, which examines previous research books and journals. Supply chain management performance measurement model found from several previous studies. The framework based on the grand theory also underlies the measurement of supply chain management performance.